1989
DOI: 10.1002/ctpp.2150290209
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Positive Column in an Argon‐Hexamethyl‐disiloxane dc Glow Discharge

Abstract: A model is presented of the positive column of a dc glow discharge in argon with small admixtures of hexamethyldisiloxane (HMDS). The axial electric field, the ion production rates for direct-, stepwise-, pair-, and Penning ionization, the densities of metastable Ar atoms and of electrons, and the wall current of HMDS ions are calculated in dependence on HMDS admixture and discharge current density. For the calculations particle balance equations were used for a diffusion determined plasma in a mixture of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Electron‐impact ionization of the monomer is a fundamental collision processes in non‐equilibrium, low‐temperature plasmas. Electron‐impact induced ionization is not only the dominant process for the formation of charge carriers in the plasma, it is also the crucial step that initiates the multitude of plasma chemical reactions through the formation of reactive neutrals and ionic radicals via dissociative ionization 28–31. Basner et al32 showed that dissociative ionization is the predominant process for complex molecules like HMDSO, where the dominant channel is the removal of the methyl group CH 3 from HMDSO to produce the ion Si 2 O(CH 3 ) 5+ with a cross section of 1.7 × 10 −15 cm 2 at 70 eV electron energy.…”
Section: Resultsmentioning
confidence: 99%
“…Electron‐impact ionization of the monomer is a fundamental collision processes in non‐equilibrium, low‐temperature plasmas. Electron‐impact induced ionization is not only the dominant process for the formation of charge carriers in the plasma, it is also the crucial step that initiates the multitude of plasma chemical reactions through the formation of reactive neutrals and ionic radicals via dissociative ionization 28–31. Basner et al32 showed that dissociative ionization is the predominant process for complex molecules like HMDSO, where the dominant channel is the removal of the methyl group CH 3 from HMDSO to produce the ion Si 2 O(CH 3 ) 5+ with a cross section of 1.7 × 10 −15 cm 2 at 70 eV electron energy.…”
Section: Resultsmentioning
confidence: 99%
“…According to Jauberteau and Jauberteau, mainly neutral radicals are produced due to collisions of metastable Ar[1s 5 ] atoms with HMDSO so that α PI is small. In contrast, 100% Penning ionization with a rate coefficient of 2.5 × 10 −10 cm 3 /s was assumed in the modelling studies of the positive column of a dc glow discharge in argon with small admixtures of HMDSO in Schmidt and Maass . The determination of the parameter α PI and the analysis of its impact on the modelling results are part of the present investigations.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…This value of α PI = 0.3 is relatively large when compared with the experimental studies in Jauberteau and Jauberteau, where mainly neutral radicals are suggested to be produced due to collisions of metastable Ar[1s 5 ] atoms. At the same time, it leads to a rate coefficient for Penning ionization k H5a = 1.5 × 10 −10 cm 3 /s, which is slightly smaller than that used in the modelling studies in Schmidt and Maass …”
Section: Analysis Of the Ignition Voltagementioning
confidence: 99%
“…Due to lack of data, Fuller's method has been used to determine approximately the reduced diffusion coefficient of precursor fragments PF in the buffer gas argon NnormalgDPF=1.46×1020 m −1 s −1 . The mobility of the fragment ions PF+ has been taken from ref . Einstein's relation Dl= μlknormalBTnormalg/ql has been applied to calculate the diffusion coefficients Dl of all ions.…”
Section: Main Features Of the Modelmentioning
confidence: 99%